Knowledge Graphs and interoperability techniques for hybrid-cloud deployment of FaaS applications - Fatouros, Georgios; Poulakis, Yannis; Polyviou, Ariana; Tsarsitalidis, Stylianos; Makridis, Georgios; Soldatos, John; Kousiouris, Georgios; Filippakis, Michael; Kyriazis, Dimosthenis (My University, 2022)
Towards enabling the automated and optimized FaaS deployment of applications in a hybrid-cloud setting, the application requirements should be met by comparing them to the capabilities of the available resources of available clusters. To this end, semantic matching between the application characteristics and the individual descriptions of available compute clusters (e.g. from public or private cloud or edge facilities available) is required. In this work, such a system is proposed, namely the Reasoning Framework, which performs semantic matching between application and resource (meta)data and facilitates information sharing among the FaaS platform components leveraging Knowledge Graphs, ontology technologies, and semantic reasoning. The proposed system harvests information from the application function workflow, provided as a graph by the function editor specification (based on Node-RED), including developer-inserted annotations during the design process, and maps them to the dynamic information retrieved from the available clusters. The Reasoning Framework interprets these data as graphs and automatically applies several semantic rules that enable filtering of the available resources and efficient information retrieval through a RESTfull interface. The paper also discusses experimental results to further showcase the advantages of the proposed approach.
Keywords: Knowledge engineering; Computers; Cloud computing; Filtering; Semantics; Information sharing; Ontologies